2013
DOI: 10.1002/app.39108
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated poly(hexamethylene terephthalate) copolyesters: Enhanced thermal and mechanical properties

Abstract: A series of poly(hexamethylene terephthalate-co-hexamethylene 5-sodium sulfoisophthalate) copolyesters containing from 5 to 50 mol % of sulfonated units as well as the two parent homopolymers are prepared by melt polycondensation. The polyesters are obtained with high molecular weights, which decrease with the increased content of sulfonated units in the copolymer. Polyesters with 5 and 10 mol % of sulfonated units are semicrystalline whereas for contents equal or above 20 mol % they are unable to crystallize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…The FTIR spectra collected between 4000 and 600 cm −1 with the corresponding peak assignments for all polyesters (Table 2 and Figure 4) are in excellent agreement with spectra previously reported for both PET [37] and FDCA-based polyesters with altering polyols [38,39,40] and sulfonated poly(hexamethylene terephthalate) copolyesters [19]. The characteristic absorbance bands of the furan rings in the FDCA-based polyesters, such as the C=C peak, appeared in the range of 1582–1578 cm −1 , the furan ring breathing around 1020 cm −1 , and the bending motions associated with the furan ring around 970, 820 and 760 cm −1 .…”
Section: Resultssupporting
confidence: 87%
“…The FTIR spectra collected between 4000 and 600 cm −1 with the corresponding peak assignments for all polyesters (Table 2 and Figure 4) are in excellent agreement with spectra previously reported for both PET [37] and FDCA-based polyesters with altering polyols [38,39,40] and sulfonated poly(hexamethylene terephthalate) copolyesters [19]. The characteristic absorbance bands of the furan rings in the FDCA-based polyesters, such as the C=C peak, appeared in the range of 1582–1578 cm −1 , the furan ring breathing around 1020 cm −1 , and the bending motions associated with the furan ring around 970, 820 and 760 cm −1 .…”
Section: Resultssupporting
confidence: 87%
“…In spite of the lack of an apparent systematic variation in the measured parameters, it can be preliminarily concluded from this analysis that the insertion of ionic sulfonated units makes the polyester stiffer but also more brittle because of the high reduction undergone in the elongation to break. This behavior is in accordance with that displayed by other ionomers containing sulfonated units that have been reported by us in previous works [2,29].…”
Section: Thermal and Mechanical Propertiessupporting
confidence: 93%
“…It was observed that the hydrolytic degradation was drastically accelerated by increasing either ionic content or pH. Similar observations have been recently reported for PBS ionenes [31] as well as for other copolyesters containing sulfoisophthalic units [2,18,29], and such increase has been attributed to the enhancement of the hydrophilicity caused by the presence of the ionic groups. Melting enthalpies displayed by PBS1, PBS95SS5 and PBS85SS15 polyesters after incubation are compared in Figure 5.…”
Section: Hydrolytic Degradationsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, the copolyesters that had the highest sulfonate content led to the lowest value of molecular weight. Sulfonated polyesters based on 1,4-butane diol (BD) and 1,6-hexane diol (HD) [13][14][15][16] were also prepared; these studies clearly show the major role of the sulfonated unit content on the copolymer chain mobility and as a consequence on Tg and hydrolytic degradation behavior. The replacement of petrochemical feedstocks by their biobased counterpart product from renewable resources in aromatic and aliphatic copolyesters has benefits relating to positive environmental impacts such as reduced carbon dioxide emissions.…”
Section: Introductionmentioning
confidence: 99%